Student and Teacher Perceptions of Student Motivation among Korean University English as a Second Language (ESL) Students - Luke Oliver Henry Allum (Indonesian TESOL Journal, 2020)
This paper analyses the differences between what teachers say motivates their students and what students say motivate them at a South Korean university. Using motivational constructs developed by Bandura and Maslow in previous motivation studies, it was determined that both teachers and students think teacher characteristics to be the most important variable motivating students, even more important than the student’s own intrinsic motivation. However, there was no agreement between students and teachers on what this looks like specifically in the classroom: teachers prefer to stimulate students’ creative thinking and to help students solve real-world problems, whereas students prefer to learn with digital media, presentations, and quizzes. Teachers and students both believe students to be highly intrinsically motivated, with the caveat that some students come to class lacking intrinsic motivation. This paper is significant in that students report teacher characteristics and instructional methodologies to be of more importance than a student’s intrinsic motivation. This paper reveals that teachers consistently over-rate the importance of teacher characteristics and methodologies on student motivation.